An integrated top-stage incubator and lens free holographic imaging system for culture monitoring applications - Özbilgin, Zeynep; Akşit, Sevdenur; Toy, Muhammed Fatih (SPIE, 2022)
Lens free inline holographic microscopy was shown to be a potent approach for many applications relying on cellular imaging. Applications requiring a large field of view at moderate resolution are the ones that are most suitable for this platform. Besides, the simplicity of the overall imaging system, which requires only a light source and a camera, positions this approach as an easily accessible one. Acquired holograms from such a system are processed to recover phase images. As an additional advantage on top of the simplicity, phase imaging enables the imaging of otherwise transparent cell samples without any need for labeling or staining. Eventually, such a system can be used for long term imaging of live cell cultures with wide field of view. Up to now, two alternatives were explored for the imaging of live cell cultures for extended duration. In one approach, a portable imaging system was placed inside a standard incubator with cell cultures on top. A stage top incubator was used on a modified microscope in the other approach. In both approaches, the cost of the system grows due to commercial systems, and the overall footprint of the system with incubator is too large to be classified as portable. Here, an integrated portable system is presented that can maintain cell cultures at desired temperature in a 3D printed enclosure while imaging them in lens free inline holographic microscopy modality. Such a system is well suited for tissue culturing and monitoring at limited resources settings.
Keywords: Cellular Imaging Systems; Digital In-Line Holographic Microscopy; Gerchberg-Saxton Algorithm; Lens Free Imaging; Numerical Reconstruction; Time-Lapse Microscopy; Top Stage Incubator